Focal adhesion kinase inhibition decreases cell viability and induces apoptosis of JAK2 V617F positive cells - Ana Carolina Menezes Mendonça Valente; Gustavo Henrique Lima de Farias; Ana Cristina Ribeiro Bernardo; Caio Cesar de Souza Alves; Michelle Bueno de Moura Pereira; Raquel Tognon-Ribeiro (Universidade de São Paulo, 2023)
Abstract Focal Adhesion Kinase (FAK) protein participates in proliferation, migration, cell survival, and apoptosis process. It has been described as overexpressed in several neoplasms being a promising target for therapy. BCR-ABL negative chronic Myeloproliferative Neoplasms (MPN) are clonal disorders characterized by the excess of proliferation and apoptosis resistance. The identification of the acquired JAK2 V617F mutation in MPN patients allowed a better understanding of pathogenesis. However, there is still no pharmacological treatment that leads all patients to molecular remission, justifying new studies. The present study aimed to evaluate FAK involvement in the viability and apoptosis of HEL and SET-2 cells, both JAK2 V617F positive cell lines. The FAK inhibitor PF 562,271 was used. Cell viability was determined using MTT assay and apoptosis verified by cleaved PARP, cleaved Caspase 3 and Annexin-V/PI staining detection. FAK inhibition significantly reduced HEL and SET-2 cells viability and induced apoptosis. Considering the role of JAK/STAT pathway in MPN, further investigation of FAK participation in the MPN cells proliferation and apoptosis resistance, as well as possible crosstalk between JAK and FAK and downstream pathways may contribute to the knowledge of MPN pathophysiology, the discovery of new molecular targets, and JAK inhibitors resistance mechanisms.